2021
DOI: 10.1017/s1352465821000382
|View full text |Cite
|
Sign up to set email alerts
|

Anger and predictors of drop-out from PTSD treatment of veterans and first responders

Abstract: Background: Drop-out is an important barrier in treating post-traumatic stress disorder (PTSD) with consequences that negatively impact clients, clinicians and mental health services as a whole. Anger is a common experience in people with PTSD and is more prevalent in military veterans. To date, no research has examined if anger may predict drop-out in military veterans or first responders. Aims: The present study aimed to determine the variables that predict drop-out among individuals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…On the other hand, a benefit of anger interventions was found in subjects with anger problems. You can therefore also benefit from such interventions before starting trauma-specific therapy ( 60 ) because anger has been shown to be a relevant factor in PTSD therapy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a benefit of anger interventions was found in subjects with anger problems. You can therefore also benefit from such interventions before starting trauma-specific therapy ( 60 ) because anger has been shown to be a relevant factor in PTSD therapy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 95 veterans and first responders found that females were more likely to drop out of a residential treatment for PTSD ( r = 0.270; overall dropout rate 59%). The number of females in this sample was small ( n = 13) [ 54 ]. Finally, an analysis of prescribing patterns for 877,785 US veterans receiving treatment for PTSD in 2019 (13.5% women) found that women were slightly more likely than men to receive antidepressants recommended for PTSD (adjusted OR = 1.07), but were also more likely to receive medications recommended against use for PTSD, including benzodiazepines (adjusted OR = 1.62), anticonvulsants (a OR = 1.41), and antidepressants recommended against use for PTSD (adjusted OR = 1.26), in analyses adjusted for comorbidities and other confounders [ 55 •].…”
Section: Rates Of Recovery and Response To Treatmentmentioning
confidence: 99%